The temperature distribution in the strand during secondary cooling of the continuously cast billet - Grozdanić, Vladimir (Materiali in tehnologije, 2004)
On the basis of mathematical model a new equation for temperature distribution in the continuous cast strand in the secondary zone has been obtained. From this equation the time of cooling of the strand surface to a selected temperature can be deduced, witch is in good agreement with experimental values from the literature.
Keywords: livarstvo; gredice; ohlajanje; porazdelitev temperature; matematični modeli